DEVELOPMENT OF PHYSICS MODULE USING MOODLE INTEGRATED LAB ROTATION IN SENIOR HIGH SCHOOL - Revielni Sandra; Pakhrur Razi (PILLAR OF PHYSICS EDUCATION, 2022)
The use of technology-based learning resources in the teaching and learning process provides benefits in increasing student independence and literacy. It can be an answer to the challenges of industrial revolution 4.0. However, realizing technology-based learning resources is still a challenge, because it is necessary to have the right learning model to achieve the desired results. Therefore, this research developed a moodle-based physics module using a rotation lab model using the ADDIE research method to answer the demands of the industrial revolution 4.0. This study aims to determine the validity and practicality of the moodle-based physics module using a rotation lab model. The moodle-based physics module using the rotation lab is in the very valid category, scoring 87. Meanwhile, in the practical aspect of the moodle-based physics module using the rotation lab model, it scored 91, which is in the efficient category.